2023
DOI: 10.3390/ijms241411637
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Ways of Nitric Oxide Production in Plants and Its Functional Activity under Abiotic Stress Conditions

Abstract: Nitric oxide (NO) is an endogenous signaling molecule that plays an important role in plant ontogenesis and responses to different stresses. The most widespread abiotic stress factors limiting significantly plant growth and crop yield are drought, salinity, hypo-, hyperthermia, and an excess of heavy metal (HM) ions. Data on the accumulation of endogenous NO under stress factors and on the alleviation of their negative effects under exogenous NO treatments indicate the perspectives of its practical application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 223 publications
1
17
0
1
Order By: Relevance
“…Given the widely accepted antagonistic interaction between JA and SA signaling, the dual upregulation of JA- and SA-related genes is noteworthy. One candidate for causing such an irregular response is NO, which is an endogenous signaling molecule crucial for plant responses to different stresses [28]. Previous studies have reported that NO induces the expression of many genes involved in oxidative stress and defense responses, including JA biosynthesis genes [29,30], SA-responsive genes [31], and genes involved in glutathione (GSH) metabolism [31,32], which correspond to the genes induced by high ammonium sulfate treatment in this study (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the widely accepted antagonistic interaction between JA and SA signaling, the dual upregulation of JA- and SA-related genes is noteworthy. One candidate for causing such an irregular response is NO, which is an endogenous signaling molecule crucial for plant responses to different stresses [28]. Previous studies have reported that NO induces the expression of many genes involved in oxidative stress and defense responses, including JA biosynthesis genes [29,30], SA-responsive genes [31], and genes involved in glutathione (GSH) metabolism [31,32], which correspond to the genes induced by high ammonium sulfate treatment in this study (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is quite plausible that endogenous NO was produced under the treatment conditions used in this study, where sufficient nitrate and excess ammonium were provided. Several reports have indicated the contribution of NO in tolerance to drought, salinity, temperature, and heavy metal stresses [28]. NO can counteract the effects of ROS produced by stresses [55] as well as alter the activity of various enzymes or TFs for stress tolerance through S-nitrosylation [56].…”
Section: Discussionmentioning
confidence: 99%
“…While nitric oxide synthesis in mammals was first described in the late 1980s [ 12 ], its synthesis in plants remains elusive due to the lack of a typical nitric oxide synthase (NOS) [ 13 ]. Possible biosynthetic pathways may include NOS-like activities of nitrate reductase (NR), nitrite reductase (NiR), and other heme-containing enzymes found in various cell organelles [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Generally speaking, nitrate reductase or NR-like enzymes are able to generate nitrite in the presence of NADPH as an electron donor; subsequently, nitrite is converted to nitric oxide by nitrite reductase or NiR-like enzymes using soluble cytochrome c or blue copper protein as electron donors [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pathways of NO generation in plants are still not fully understood [ 13 ]. The possible substrates for the oxidative mechanism of NO production are L-arginine via nitric oxide synthase-like (NOS-like) activity, polyamines (PAs), and hydroxylamines (HAs) [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%